Peripheral imbalanced TFH/TFR ratio correlates with intrathecal IgG synthesis in multiple sclerosis at clinical onset. (June 2019) - Puthenparampil, Marco; Zito, Antonio; Pantano, Giorgia; Federle, Lisa; Stropparo, Erica; Miante, Silvia; De Silvestro, Giustina; Plebani, Mario; Gallo, Paolo
Background: Alteration of T-follicular helper (TFH) and regulatory (TFR) subpopulations may contribute to the development of auto-reactive B-cell. Objective: To investigate whether changes in TFH and TFR subsets are associated with abnormal IgG synthesis in blood and cerebrospinal fluid (CSF) of multiple sclerosis (MS) patients. Methods: Paired blood and CSF samples were obtained from 31 untreated relapsing-remitting multiple sclerosis (RRMS) patients at diagnosis. Peripheral blood TFH (CD3+CD4+CXCR5+CD25–CD127+), TFR (CD3+CD4+CXCR5+CD25+CD127 dim ), conventional T-Helper (TH, CD3+CD4+CXCR5–CD25–CD127+), and regulatory T-cells (T-Reg, CD3+CD4+CXCR5–CD25+CD127 dim ) were analyzed in all RRMS patients and in 13 healthy controls (HCs). Qualitative and quantitative intrathecal IgG synthesis was evaluated in RRMS patients, who were then further subclassified according to the presence of IgG oligoclonal bands in blood and/or CSF. Results: Compared to HC, RRMS had lower TFR percentage ( p < 0.01) and higher TFH/TFR ratio ( p < 0.001). In RRMS, TFH/TFR ratio correlated with both qualitative ( r = 0.56, p < 0.005) and quantitative intrathecal IgG synthesis (IgG Index: r = 0.78; IgGLoc: r = 0.79; IgGIF: r = 0.76, all p < 0.001). Patients with the highest TFH/TFR ratios had higher percentages of circulating B-cells (36.1 ± 35.2%, p < 0.05). Conclusion: In RRMS, increased TFH/TFR ratio associates with abnormal IgG production in blood and CSF, suggesting that antibody-producing cells, derived from deregulated peripheral germinal center reaction, colonize the CNS.